IMPLEMENTASI PROGRAM LITERASI DALAM MENANGGULANGI KESULITAN SISWA MADRASAH ALIYAH PADA ASESMEN KOMPETENSI MINIMUM - Rizki Nur Faoziyah; Umar Dani; Sevty Sheyla Kharami (JENTRE, 2023)
This study seeks to describe the literacy curriculum in MAN 1 Bogor as a solution dealing with the Minimum Competency Assessment (AKM). AKM is one of the primary instruments of the National Assessment that serves as a replacement for the National Examination and provides data for mapping and evaluating the education system.  AKM is administered to pupils at all levels of education, including grade 4 elementary school, grade 8 junior high school, and grade 11 high school / vocational school with varying levels and question counts.  The results of AKM can depict the actual state of students' mastery of reading and numeracy literacy skills.  This form of research is qualitative and descriptive. The participants are pupils enrolled in AKM MAN 1 Bogor, West Java, for the 2021/2022 academic year.  Interviews and questionnaires were used to collect information for this study. 81% of the respondents at MAN 1 Bogor demonstrated the need for an adult literacy program. Three students with varying levels of ability were also interviewed to strengthen the research findings